The Correlation between Revised Trauma Score (RTS) and Head Injury Mortality in the Emergency Room - Cicilia Sari Padaruntung; Rivan Firdaus; Arifin Hidayat (Formosa Journal of Science and Technology, 2023)
Revised Trauma Score (RTS) is an assessment of the human physiological system as a whole. The use of the RTS method in the IGD Harapan Insan Sendawar Hospital has not been optimally implemented. This study aims to determine the relationship between RTS and head injury mortality. The type of research used is quantitative research, using a correlation analytic design with a cross sectional approach to 30 respondents. Sampling by nonprobability sampling with total sampling technique. Data collection using the RTS observation sheet. Data were analyzed univariately and bivariately by using the chi square test and followed by an alternative fisher's exact test. Obtained variable value ρ value = 0.000 which is smaller than the value of α = 0.05 Then Ho is rejected and Ha is accepted, so there is a relationship between Revised Trauma Score and head injury mortality. So it can be concluded that there is a relationship between Revised Trauma Score (RTS) and head injury mortality. It is suggested that the Hospital is able to improve the application of the Revised Trauma Score (RTS) assessment.